The influence of the real effective exchange rate and relative prices on South Africa's import demand function: An ARDL approach - Tony Nchokoe Matlasedi (Cogent Economics & Finance, 2017)
This paper analyses the influence of the real effective exchange rate (REER) and relative prices on South Africa's import demand function both in the long run and the short run. The ARDL bounds testing approach is employed to test the long-run relationship hypothesis. The estimation of both the long-run and short-run import demand models is based on the ARDL error correction methodology. All the tests are applied to South Africa's secondary quarterly data covering the period 1980Q1-2014Q4. Real GDP and Foreign reserves were also added to the models as control variables. The Bounds test proved cointegration and the results show that in the long run, South Africa's import demand is negatively related to the REER, while being positively related to Real GDP (used as a proxy for national income) and relative prices. The coefficient of the relative price variable is greater than 1 in absolute terms, thus also confirming the Marshal Lerner condition. In the short run, import demand is found to be negatively related to the REER, while being positively related to Real GDP, relative prices and the stock of foreign reserves. The result gives hope that a policy aimed at depreciating the currency may help bring down the surge in import demand.
Keywords: C32; F13; F31; 330; import demand; foreign exchange; depreciation; auto regressive distributed lag model (ARDL); commercial policy; Marshall-Lerner condition